Shaping a Global Theological Mind. - Marks, Darren C (Ashgate Pub, 2008)
Theological thinkers are placed into contexts which inform their theological tasks but that context is usually limited to a European or North American centre, usually ignoring minorities and lesser mainstream theologies even in that context. This work focuses on the shift of Christian theological thinking from the North Atlantic to the Global South, even within the North Atlantic Church and Academy. It gives a Global perspective on theological work, method and context. Theologians from North America, Great Britain and Europe, Africa, Asia, Central and South America comment on how their specific context and methodology manifests, organizes and is prioritized in their thought so as to make Christian theology relevant to their community. By placing the Global South alongside the newly emerging presence of non-traditional Western forms such as Pentecostal, Aboriginal, and Hispanic theologies and theologians a clearer picture of how Christian theology is both enculturated and still familial is offered.